The five years financial analysis of MAINS Holdings Sdn Bhd (MHSB) / U’mi Nona A’mar Amir - Amir, U’mi Nona A’mar (2010)
Financial analysis is conducted to assess the value of a firm for the purpose of buying or selling its shares, lending, acquiring the company, leasing equipment, entering into or terminating some contract. Value is defined as the sum of future benefits of the decision maker derived from earnings, proceeds from the sale, interest from the loan or some other flow of cash. Value, like beauty, is very much in the eyes of the beholder. For each decision maker, future benefits are different. Hence, there isn't a single measure of value. The assessment of value differs according to the purpose an analyst has for conducting the analysis. This study analyzes MAINS Holdings Sdn Bhd (MHSB) financial statement from year 2005 until 2009 using comparative analysis on both methods, which is comparative analysis year to year method, comparative analysis index number trend method, common size analysis method and finally, financial analysis method. This study was carried out by researcher using MHSB original financial statements to ensure whether MHSB financial condition able to meet their objective and mission in helping Muslim small entrepreneur, Negeri Sembilan Muslim economic importance and helping needed by implementing Mua’malah concept in economic and business activities. The findings of this study show that even though MHSB revenue and net income decreasing and fluctuating, respectively every year, but MHSB able to maintain sound their liquidity condition and able to reducing their capital structure and solvency.